Republication of “Peroneus Brevis Tenodesis: Side-to-Side or Weave?” - Cory F. Janney MD, MC, USN; Michael Iloanya BA; Randal Morris BS; Vinod K. Panchbhavi MD, FACS (Foot & Ankle Orthopaedics, 2023)
Background: Inversion ankle injuries are extremely common, sometimes causing injury to the peroneus brevis tendon. If more than 50% of the tendon is injured, it oftentimes requires tenodesis to the adjacent peroneus longus tendon. Both Pulvertaft (PT) and side-to-side (SS) techniques have been used for joining the 2 tendons. The purpose of this study was to compare the strength and stiffness of these 2 techniques. Methods: Five matched pairs of cadaver ankle specimens were randomized to receive either an SS or PT tenodesis of the peroneus brevis to longus tendons. Following the tenodesis, the specimens were tested for failure load, displacement, energy absorbed at failure, and peak load. Stiffness was also calculated. Paired t tests were performed to detect differences between the 2 conditions. Results: There were no statistically significant differences between the SS and PT tenodesis for any of the metrics measured. For stiffness, the techniques were very similar (SS = 10.14 [4.35], PT = 12.85 [1.72]). Conclusion: There is no difference in failure load, displacement, energy absorbed at failure, peak load or stiffness between the PT and SS techniques for peroneal tenodesis. Level of Evidence: Level V, cadaver study.